Design and synthesis of dual 5-HT1A and 5-HT7 receptor ligands. Issue 16 (15th August 2016) - Ofori, Edward; Zhu, Xue Y.; Etukala, Jagan R.; Peprah, Kwakye; Jordan, Kamanski R.; Adkins, Adia A.; Bricker, Barbara A.; Kang, Hye J.; Huang, Xi-Ping; Roth, Bryan L.; Ablordeppey, Seth Y.
Graphical abstract: Abstract: 5-HT1A and 5-HT7 receptors have been at the center of discussions recently due in part to their major role in the etiology of major central nervous system diseases such as depression, sleep disorders, and schizophrenia. As part of our search to identify dual targeting ligands for these receptors, we have carried out a systematic modification of a selective 5HT7 receptor ligand culminating in the identification of several dual 5-HT1A and 5-HT7 receptor ligands. Compound16, a butyrophenone derivative of tetrahydroisoquinoline (THIQ), was identified as the most potent agent with low nanomolar binding affinities to both receptors. Interestingly, compound16 also displayed moderate affinity to other clinically relevant dopamine receptors. Thus, it is anticipated that compound16 may serve as a lead for further exploitation in our quest to identify new ligands with the potential to treat diseases of CNS origin.